Adaptive Leadership in Character Education: Insights from SMP Negeri 3 Kasihan, Bantul, Indonesia - Pratiwi, Annisa Rizki; Sibawaihi (Journal of Islamic Education Management Research, 2023)
Purpose  – This research examines the pivotal role played by the Head of SMP Negeri 3 Kasihan in implementing character education strengthening. It seeks to explore the process of implementing character education, shedding light on the key supporting and inhibiting factors during the Industrial Revolution era 4.0 and the challenges posed by the COVID-19 pandemic. Design/methods/approach  – Conducted as a qualitative study, this research utilized a field survey approach employing descriptive analysis. The study occurred at SMP Negeri 3 Kasihan and used data collection methods such as observation, interviews, and documentation. An inductive method was applied, concluding specific facts to generalize findings. Findings  – The research findings reveal three main points: (1) The Head of the school serves various roles, including manager, educator, administrator, supervisor, leader, and innovator, in implementing character education strengthening. (2) In the era of Industry 4.0, the process involves personality development through scouting and the introduction of technology. Character-strengthening education was conducted during the pandemic through distance, online, and blended learning. (3) Students adapt to the times, with online implementation a significant supporting factor. However, challenges include suboptimal material delivery and a lack of direct monitoring due to the online learning environment. Research implications/limitations  – The impact of this research extends to educational policymakers and practitioners, emphasizing the multifaceted role of school leaders in character education. Rules include the specific context of SMP Negeri 3 Kasihan and the challenges the online learning environment poses. Practical implications  – The study underscores the need for adaptive approaches in character education implementation, recognizing the role of school leaders as crucial in overcoming challenges, especially in the context of the Industrial Revolution era 4.0 and the pandemic. Originality/value  – This research contributes to the literature by providing insights into the specific challenges and strategies the Head of SMP Negeri 3 Kasihan employs in implementing character education during dynamic times. The study's originality lies in examining the dual impact of Industry 4.0 and the pandemic on character education, offering valuable lessons for educational institutions navigating similar challenges.